1987
DOI: 10.1152/ajpregu.1987.252.2.r361
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of major artery segments of rat by fish neuropeptide urotensin II

Abstract: Urotensin II (U II) caused marked concentration-dependent contractions of helical strips from several major arteries of the rat. The thoracic aorta was most sensitive; the apparent concentration of U II producing half-maximal contraction was 6.8 X 10(-10) M. Papaverine, dibutyryl cyclic AMP, forskolin, and nitroprusside antagonized the contractile responses to U II at the apparent concentrations producing 50% inhibition (IC50) of 7.6 X 10(-6), 2.1 X 10(-4), 2.5 X 10(-6), and 1.5 X 10(-8) M, respectively. Verap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 0 publications
8
59
1
Order By: Relevance
“…In accord with previous studies performed using the goby isoform of U-II in ®sh, amphibian and mammalian (rat and rabbit aortae) isolated vascular tissue (Muramatsu et al, 1979;Gibson, 1987;Gibson et al, 1988;Itoh et al, 1987;1991;Conlon et al, 1996), potent, sustained and e cacious vasoconstriction was observed upon exposure of speci®c rat, dog, pig and primate isolated blood vessels to the human isoform of U-II (Table 5). Indeed, human U-II was between 8 and 109 fold more potent than ET-1.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In accord with previous studies performed using the goby isoform of U-II in ®sh, amphibian and mammalian (rat and rabbit aortae) isolated vascular tissue (Muramatsu et al, 1979;Gibson, 1987;Gibson et al, 1988;Itoh et al, 1987;1991;Conlon et al, 1996), potent, sustained and e cacious vasoconstriction was observed upon exposure of speci®c rat, dog, pig and primate isolated blood vessels to the human isoform of U-II (Table 5). Indeed, human U-II was between 8 and 109 fold more potent than ET-1.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis is supported by the recent identi®cation of U-II isopeptides in the rat, mouse, pig and man (Ames et al, 1999;Coulouarn et al, 1998;Mori et al, 1999). The present study has evaluated the functional activity of human U-II in a range of native vascular tissue isolated from a variety of mammals.In accord with previous studies performed using the goby isoform of U-II in ®sh, amphibian and mammalian (rat and rabbit aortae) isolated vascular tissue (Muramatsu et al, 1979;Gibson, 1987;Gibson et al, 1988;Itoh et al, 1987;1991;Conlon et al, 1996), potent, sustained and e cacious vasoconstriction was observed upon exposure of speci®c rat, dog, pig and primate isolated blood vessels to the human isoform of U-II (Table 5). Indeed, human U-II was between 8 and 109 fold more potent than ET-1.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with these data, it has previously been reported that UII inhibits carbachol-induced contraction of the anococcygeous muscle (44) and that dbcAMP and forskolin counteract the contractile response evoked by UII in rat aortic strips (45). UII has also been shown to lower cytoplasmic free Ca 2þ concentration in goby enterocytes (46).…”
Section: Discussionsupporting
confidence: 79%